Somatotype, size and body composition of competitive female volleyball players - Malousaris, G. G.; Bergeles, N. K.; Barzouka, K. G.; Bayios, I. A.; Nassis, G. P.; Koskolou, M. D. (Journal of Science and Medicine in Sport, 2008)
The aim of this study was to describe the morphological characteristics of competitive female volleyball players. For this purpose, body weight and height, breadths and girths as well as skinfold thickness at various body sites were assessed in 163 elite female volleyball players (age: 23.8±4.7 years, years of playing: 11.5±4.2, hours of training per week: 11.9±2.9, means±S.D.). Seventy-nine of these players were from the A1 division and the rest from the A2 division of the Greek National League. Two-way ANOVA was used to compare the differences in these characteristics between competition level and playing position. Body height ranged from 161 cm to 194 cm, and the mean value (177.1±6.5 cm) was not inferior to that of international players of similar calibre. Adiposity of these players (sum of 5 skinfolds: 51.8±10.2mm, percent body fat: 23.4±2.8) was higher than that reported in other studies in which, however, different methodology was used. Volleyball athletes of this study were mainly balanced endomorphs (3.4-2.7-2.9). The A1 division players were taller and slightly leaner with greater fat-free mass than their A2 counterparts. Significant differences were found among athletes of different playing positions which are interpreted by their varying roles and physical demands during a volleyball game. The volleyball players who play as opposites were the only subgroup of players differing between divisions; the A2 opposites had more body fat than A1 opposites. These data could be added in the international literature related to the anthropometric characteristics of competitive female volleyball players.